Research on biomimetic design and impact characteristics of periodic multilayer helical structures - Liu, Yu-Xi; Li, Ai-Hua; Lin, Shi-Yun; Sun, Hong; Chen, Bin (Frontiers in Bioengineering and Biotechnology, 2023)
Osteons are composed of concentric lamellar structure, the concentric lamellae are composed of periodic thin and thick sub-lamellae, and every 5 sub-lamellae is a cycle, the periodic helix angle of mineralized collagen fibers in two adjacent sub-lamellae is 30°. Four biomimetic models with different fiber helix angles were established and fabricated according to the micro-nano structure of osteon. The effects of the fiber periodic helical structure on impact characteristic and energy dissipation of multi-layer biomimetic composite were investigated. The calculation results indicated that the stress distribution, contact characteristics and fiber failur during impact, and energy dissipation of the composite are affected by the fiber helix angle. The stress concentration of composite materials under external impact can be effectively improved by adjusting the fiber helix angle when the material composition and material performance parameters are same. Compared with the sample30, the maximum stress of sample60 and sample90 increases by 38.1% and 69.8%, respectively. And the fiber failure analysis results shown that the model with a fiber helix angle of 30° has a better resist impact damage. The drop-weight test results shown that the impact damage area of the specimen with 30° helix angle is smallest among the four types of biomimetic specimens. The periodic helical structure of mineralized collagen fibers in osteon can effectively improve the impact resistance of cortical bone. The research results can provide useful guidance for the design and manufacture of high-performance, impact-resistant biomimetic composite materials.